The Critical Discourse Analysis of Translation Shift from the Word Use of Al-Quds to Jerusalem in Republika - Aryana Rahman; Apipuddin Apipuddin (Proceedings of AICS - Social Sciences, 2018)
The use of word to describe Palestine becomes the background of this research. The Qur'an and other holy books use the word Palestine equivalently to Al-Quds, Al-Aqsa, the blessed country, the holy city, the Promised Land, and Darussalam (Jerusalem). However, lately in the global world, social media, and international forums, the Palestinian capital has been widely replaced with Jerusalem. This study aims to understand and analyze the shift in meaning and the discourse that was built in it. The data contained in this study comes from documents Republika online. This study uses critical discourse analysis theory from Norman Fairclough and the theory of translation shift from Abdul Chaer. From the analysis, it is concluded that the Al Quds or Jerusalem allegations are inseparable from the geopolitical dominance of Israel and the mastery of mass media information which is oriented towards either Israel or Palestine. In addition, if it is equated linguistically, Jerusalem is a translation of the word Darussalam. Darussalam in the terminology of the Qur'an is a land of full of blessings, so that be said the use of the word of Jerusalem is linguistically accurate. This research concludes that Republika online uses more of ‘Al-Quds’ word compared to ‘Jerusalem’ in news publication about Palestine. This research also found that there has been a narrowing of meaning interpretation the word ‘Al-Quds’ to become ‘Jerusalem’. This research hopes that pragmatics theory would be developed in as much as many of unwritten things dominate more, formality of linguistic units even give birth to new semantic.Keywords:Al Quds, Jerusalem, semantic change, critical discourse analysis.